Application of higher dimensional theories to cosmology - Goo, Joseph Wei Zhen (Nanyang Technological University, 2023)
This thesis discusses the electroweak theory, which unifies the electromagnetic and weak nuclear forces, but has several problems such as the origin of Higgs potential, hierarchy, fine-tuning, and vacuum energy. The Minimal Supersymmetric Standard Model (MSSM) is proposed as a candidate for physics beyond the Standard Model, which solves some of these problems and provides a candidate for dark matter. However, MSSM does not describe gravity, which leads to the need for a unified theory of Quantum Field Theory and General Relativity. String theory, which proposes that the fundamental objects in nature are one-dimensional strings, is introduced as a possible solution. The thesis also discusses the Dvali-Gabadadze-Porrati (DGP) braneworld model of dark energy, motivated by superstring theory. The thesis is divided into five parts, covering electroweak theory, supersymmtry, string theory, DGP model, and conclusion.